Gender Code – A Narrative Ethical Glance At Women Developers In Finnish Information Technology - Kronqvist, Aila; Rousi, Rebekah (Design Research Society, 2024)
The Information Technology (IT) sector is the current Athens of all industry. It is no longer geeky, but chic, defining the modes and limits of modern civilization. IT in its numerous forms provides the vehicle of expression and citizenship in contemporary times. While more women designers and developers enter the field are they experienc-ing a stronger sense of equality? This paper reports a narrative inquiry that probed the experiences of women professionals in the IT field. Particular attention was placed on how females entered the field, the roles and tasks that they often found themselves undertaking, and social factors in organizational communication that were specific to being female in the field. The results indicate biased conditions. Historical discourse promoting men as creative and intellectual (I.e., technical) still thrives and women are seen as administrators (crafts people). The paper ponders how these social dynamics affect the cognitive-affective processes of women developers.
Keywords: ethics; design; profession; women; information technology; gender; fi=Viestintätieteet|en=Communication Studies|